Герменевтические подступы к русской литературе - Szubin, Roman (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article is devoted to the search for a new space in the methodological studies on Russian literature. The author takes as its basis the method of hermeneutics of words by Vardan Hayrapetyan. Especially the basic categories such as the world man (homo mundi), the Other and its variants: the self (rus. самость), otherness (rus. другость), the alien (rus. чужесть) and two triads, which postulate two types of intellectual situations. In this regard, the author identifies the concept of the hybrid man of the hero of Russian literature in which a small person is a representative of an impersonal collective personality of the world man, home, family, ideas, etc. The author demonstrates the type of a hybrid man on the example of the protagonist of the novel by Vasily Shukshin Stepan Razin.